Efficacy of nasal dressings and applications for postoperative management following sinus surgeries: a systematic review and meta-analysis - Zhang, Yali; Wen, Liang; Xu, Chun chun; Shi, Xia mi; Kan, Wenwu; Chen, Li (Frontiers in Surgery, 2025)
BackgroundPostoperative complications such as crusting, synechiae, bleeding, and infection are common following sinus surgeries. Various local and systemic interventions have been proposed to optimize healing and improve patient outcomes, yet the comparative efficacy of these strategies remains unclear.ObjectiveTo evaluate and compare the clinical efficacy of different postoperative applications, including nasal dressings, irrigation methods, topical medications, and systemic therapies, used after sinus surgeries.MethodsA systematic review and meta-analysis were conducted following PRISMA guidelines. PubMed, Scopus, and Web of Science were searched to identify studies assessing postoperative interventions in patients undergoing nasal or sinus surgeries. A total of 30 studies comprising 30 randomized controlled trials were included. Interventions were categorized into four groups: nasal dressings, nasal irrigation, topical sprays/ointments, and systemic therapies. Outcomes such as endoscopic healing scores, crusting, synechiae formation, bleeding, infection, and patient-reported symptom scores (e.g., SNOT-22) were analyzed. Publication bias was assessed using funnel plots and Egger's test.ResultsNasal dressings, particularly bioabsorbable materials impregnated with corticosteroids or antibiotics, consistently improved mucosal healing and reduced crusting and synechiae formation. Buffered hypertonic and antiseptic nasal irrigation showed superior symptom relief and microbial clearance compared to isotonic saline. Topical therapies provided adjunctive benefits in reducing inflammation, while systemic therapies offered limited additional efficacy. Subgroup analyses indicated that intervention effectiveness varied by surgery type. Minimal publication bias was observed.ConclusionThis review highlights the superiority of locally applied, multimodal interventions for optimizing postoperative outcomes in nasal and sinus surgeries. Systemic therapies may be reserved for select indications. These findings support the need for tailored postoperative care protocols and the standardization of outcome measures in future clinical trials.